1989
DOI: 10.1111/j.1469-8137.1989.tb00310.x
|View full text |Cite
|
Sign up to set email alerts
|

The biology of mycorrhiza in the Ericaceae

Abstract: Sl'M MARY[lyntenoscvplius ericae utilizes protein as a sole source of nitrogen through tbe production of an extraccllular proteinase. A sensitive procedure for assay of tbe enzyme is described and is used to detern-iine tbe major characteristics of tbe enzyme. Tbe enzyme bas a sharp pi I optimum at 2-2 with little activity above pH 5-0. \'akics for K and I',,.,^ of tbe enzyme were determined.Pepstatin, a specific inhibitor of carboxyl (acid) proteinascs, almost completely inhibited activity, coiiHrming that th… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
33
0
1

Year Published

1990
1990
2024
2024

Publication Types

Select...
5
3

Relationship

1
7

Authors

Journals

citations
Cited by 76 publications
(35 citation statements)
references
References 16 publications
1
33
0
1
Order By: Relevance
“…With regard to inactivation or breakdown, it is possible that protein secreted into the medium is later subjected to proteolysis, the products of which are then re-absorbed by the fungus. The production of proteases was not followed in this study; however, the production of extracellular protease by H. erieae in liquid culture has been demonstrated elsewhere (Leake & Read, 1989, 1990a. Using liquid cultures, albeit with a different medium to that described here, Leake & Read (1989) showed that protease production is maximal at 4 d after inoculation, decreasing to a minimum after 9 d. It is possible that similar temporal variation in the appearance of extracellular protease activity is responsible for the disappearance of y5-l,4-endoxylanase activity seen in the liquid cultures described in this paper.…”
Section: Resultsmentioning
confidence: 99%
See 1 more Smart Citation
“…With regard to inactivation or breakdown, it is possible that protein secreted into the medium is later subjected to proteolysis, the products of which are then re-absorbed by the fungus. The production of proteases was not followed in this study; however, the production of extracellular protease by H. erieae in liquid culture has been demonstrated elsewhere (Leake & Read, 1989, 1990a. Using liquid cultures, albeit with a different medium to that described here, Leake & Read (1989) showed that protease production is maximal at 4 d after inoculation, decreasing to a minimum after 9 d. It is possible that similar temporal variation in the appearance of extracellular protease activity is responsible for the disappearance of y5-l,4-endoxylanase activity seen in the liquid cultures described in this paper.…”
Section: Resultsmentioning
confidence: 99%
“…Ericoid mycobionts produce little mycelium external to the root, and there is much evidence advocating enzyme-mediated degradation of organic nitrogen and, to a lesser extent, phosphorus compounds as the basis of the enhanced plant growth arising from the symbiosis (Read, 1992). Thus Leake & Read (1989, 1990a) have clearly demonstrated extracellular proteolytic enzymes associated with ericoid endophytes, and Mitchell & Read (1981) and Straker & Mitchell (1986) provide evidence of extracellular phosphatase activities.…”
Section: Introductionmentioning
confidence: 99%
“…Previous work has shown that ericoid mycorrhizas can use protein as an N source by excretion of protease into the medium (Leake & Read, 1989). Ames et al (1984) demonstrated that AM-colonized sorghum (Sorghum bicolor) can use an organic source of N, although no protease excretion has been found in AM symbiosis.…”
Section: Discvssionmentioning
confidence: 99%
“…1 paper, and the mycelium was then oven dried at 80 °C for 24 h and weighed. The culture filtrate was assayed for extracellular proteinase activity using an adaptation of the casein-fluorescein isothiocyanate (casein-FITC) method of Twining (1984), as described by Leake & Read (1989).…”
Section: Assay Of Enzyme Activitymentioning
confidence: 99%
“…However, the extracellular proteinase produced by cultures of H. ericae grown at pH 3-5 with bovine serum albumin (BSA) as sole N source has a well-defined, extremely acidic pH optimum at pH 2-2, with negligible activity at pH values of 4-0 and above (Leake & Read, 1989). On the basis of these observations, it has been suggested (Leake & Read, 1989) that the responses to pH reported by Bajwa et al (1985) represent the combined effect of pH on enzyme production and activity.…”
Section: Introductionmentioning
confidence: 99%